Flexural strengthening of beams with large Opening in critical bending zone (static conditions) - Preetpal Kaur a/p Ragbir Singh, Preetpal Kaur (2010)

(untitled)
This research study was conducted to investigate the flexural strengthening of concrete beams with large opening using CFRP strips. The principal focus was given to determine the effects of the circular and square shape of openings. The amount and configuration of CFRP strips was determined based on the failure behaviour of the corresponding beam without strengthening. The amount of opening (circular and square) was kept as 8% - 10% of the beam elevation. The circular opening caused about 3.5% load capacity loss as compared to the solid beam and square opening resulted in about 22% loss of capacity. After applying CFRP on the circular opening beam; the capacity was obtained as 64% higher than the capacity of the solid beam. Whereas with square openings; CFRP application increased the capacity by 14% with respect to the solid beam. After applying CFRP on the circular opening beam; the capacity was obtained as 67% higher than the capacity of the circular opening beam without CFRP strips. Whereas with square openings; CFRP application increased the capacity by 11% with respect to the square opening beam without CFRP strips.